Bridging the TPACK Gap: AI Integration in Iranian EFL Context - Khodadust, Mohammad Reza; Khodadoust, Azin; Faramarzi Kohnehshahri, Fatemeh; Hashemi, Somayyeh (AI and Tech in Behavioral and Social Sciences, 2026)
This mixed-methods study, grounded in the Technological Pedagogical Content Knowledge (TPACK) framework, explores Iranian EFL teachers' perceptions and experiences regarding AI integration. Combining a systematic literature review with survey data from 25 teachers, the research reveals strong enthusiasm for AI’s potential to enhance personalization, engagement, and efficiency. However, significant barriers impede effective implementation: pronounced ethical concerns regarding data privacy and bias, a critical need for pedagogical training aligning AI with language teaching goals, and marked disparities in access between well-resourced and underfunded institutions. Qualitative insights further emphasized demands for equitable tool access and strategies preserving essential human interaction, reframing AI as a scaffold rather than a replacement. The findings highlight a critical TPACK misalignment, where contextual constraints dominate. The study concludes that realizing AI's potential requires TPACK-aligned professional development, policy interventions bridging resource gaps, and collaborative frameworks balancing innovation with socio-emotional learning. Implications hold global relevance for similar educational contexts.